Vertebral Anatomic Variations in Thoroughbred Racehorses in Trinidad - Reda Mohamed (مجلة الانبار للعلوم البيطرية)
Reports of the occurrence of lumbar vertebrae variants in horses in Trinidad are rare in the literatures. Parts of the skeletons of two horses of unknown age and sex that died in a horse farm in Trinidad and Tobago were brought to the Anatomy laboratory. It was reported that specimens of fused left transverse processes of the 5th and 6th lumbar vertebrae and a blunted left transverse process of the 6th lumbar vertebra in thoroughbred racehorses in Trinidad.